Penerapan Prinsip Kerja Sama Komunikasi dan Prinsip Sopan Santun Bahasa Arab Santriwati Pondok Modern Arrisalah - Jepri Nugrawiyati; Lutvi Ali Sahana Anggian (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
The Student of Arrisalah International College comes from various tribes in Indonesia, its make the style of language also varies according to each region.but in the college environment, the students use Arabic and English for daily communication. Whereas when language violations will be sanctionedaccording to the violations committed. Thus the students will be accustomed to orderly language rules. Based on this background, research was carried out onthe application of the principle of cooperation and the principle of manners in students Arabic communication in Arrisalah International College. Theresearcher uses a pragmatic approach with qualitative research design to get the information of the problems. The research data was obtained from naturalsettings by observation, field notes and interviews. With regard to the formulation of the first problem, analysis of data generates conclusions. The forms of cooperation in Arabic language communication among female students in Modern Arrisalah huts are (1) maxim of quantity, (2) maxim of quality, (3)maxim of relevance, and (4) maxim of method. Furthermore, with regard to the second problem which shows the form of Arabic language manners the studentsof Arrisalah are (1) the principle of generosity, (2) the principle of wisdom, (3) the principle of appreciation, (4) the principle of consensus, and (5) the principleof conclusions.Keywords: Language style, cooperation, politeness